Possibilities of using natamycin in the treatment of vulvovaginal candidiasis - Yu.E. Dobrokhotova; I.I. Ivanova (LCC «Medicine-Inform», 2018)
Possibilities of using natamycin in the treatment of vulvovaginal candidiasis Yu.E. Dobrokhotova1, I.I. Ivanova2 1 Pirogov Russian National Research Medical University, Moscow, Russian Fegeration 2 CDC "Medsi in Krasnaya Presnya", Moscow, Russian Fegeration One of the most frequent causes of women's applying to a doctor is the lesions of the vaginal mucous membrane and external genital organs, caused by yeast-like fungi - candidiasis vulvovaginitis (CVV). 75% of women during the life have at least one, and 40-45% - two or more CVV episodes. Treatment of CVV is complicated by the fact that most often candidiasis is a marker of various pathological conditions (immunodeficiency disorders, dyshormonal disorders, etc.). In this regard, in parallel with antimycotic therapy, it is necessary to correct the conditions leading to the development of CVV. Aim: comparison of subjective and laboratory parameters before and after treatment of acute CVV with Primafungin (natamycin) (JSC «Avexima», Russia). Patients and Methods: 30 women of reproductive age with acute CVV manifestations participated in the study. The efficacy of using Primafungin (natamycin) - 100 mg intravaginally for 3 days was assessed. The diagnosis was established on the basis of complaints and the results of dynamic microscopic examination. Results: before the treatment, the patients mostly had complaints of itching and burning in the genital area, less frequently - of hyperemia of the vulva and leucorrhea. The smear tests microscopy revealed that the vaginal microflora was mainly represented by cocci, Candida albicans was detected in more than half of the patients. After treatment, the complaints of the patients substantially regressed. According to the microscopic examination of vaginal smears, the frequency of Candida albicans decreased and microflora normalized. Primafungin showed a good tolerability during the study, no adverse reactions were recorded. Conclusion: treatment with the use of Primafungin showed its positive result of treatment - the clinical efficacy was 91%, mycological eradication was 96%. A short treatment course with Primafungin (for 3 days) promotes a high compliance with the therapy. The drug can be recommended for the treatment of patients with acute CVV. Key words: candidiasis vulvovaginitis, CVV, vaginal discharge, microflora, natamycin, Primafungin. For citation: Dobrokhotova Yu.E., Ivanova I.I. Possibilities of using natamycin in the treatment of vulvovaginal candidiasis. Russian journal of Woman and Child Health. 2018;1(1):76-81.